ESCAPEE ORNAMENTAL PLANTS: EFFECT ON SPECIES DIVERSITY IN THE ADJOINING VEGETATION OF THE PARKS AND GARDENS, UNIVERSITY OF LAGOS, NIGERIA - Sanyaolu, V. T; Ogunyemi, S, Awodoyin, R. O; Ayodele, A. E (UNILAG Journal of Medicine, Science and Technology, 2020)
This study identified invasive species amongst the escapee OPs and determined their effects in the adjoining vegetation (AV) of the Parks and Gardens, University of Lagos, Nigeria. Species enumeration was done across the AV and an uninvaded vegetation located within the garden using systematic sampling technique in two consecutive years during dry (D1, D2) and wet (W1, W2) seasons. Escapee OPs were identified and Relative Importance Value (RIV) of plants were determined. Community structure was established using Shannon-Wiener (H’) and Equitability (J) indices. Comparison of species was carried out using Jaccard’s similarity coefficient (SCJ). Results obtained revealed more individuals in the dry seasons and more in wet seasons for invaded and uninvaded vegetation respectively. A total of 59 species in 36 families occurred in invaded vegetation and 67 species in 39 families in the uninvaded vegetation. Diffenbachia seguine (Jacq.) Schott was the most important species in the invaded AV in all four seasons with mean RIV of 19.5%. In the uninvaded vegetation, mean RIV were low, ranging between 0.21% - 3.41%. Species diversity indices, H’ and J were 2.39 - 3.03 and 0.69-0.71 respectively for invaded vegetation and 3.94-4.04 and 0.97 in all seasons respectively for uninvaded vegetation. SCJ ranged between 40.0-60.0% in the invaded vegetation and 84.4-90.1% in the uninvaded vegetation. Twelve OPs escaped into the AV. Among these, only four; Diffenbachia seguine, Synogonium podophyllum Schott, Heliconia psittacorum L.f. and Epipremnum pinnatum (L.) Engl. were invasive. Their invasion resulted in low species diversity in the adjoining vegetation.